A multi-perspective comparison for selection between system dynamics and discrete event simulation. (7th July 2010) - Chahal, Kirandeep; Eldabi, Tillal
System dynamics (SD) and discrete event simulation (DES) are two established simulation techniques for simulating the dynamics of a system. Both have been widely used in modelling business decisions. This paper presents meta-comparison between the two approaches based on literature survey. Upon reviewing the existing literature it has been identified that existing comparisons could be classified under three main perspectives: systems perspective, problems perspective and methodology perspective. The nature of system and nature of problem have been argued as primary factors for deciding modelling methodology. Therefore SD and DES comparisons have been classified on the basis of systems, problems and inherent aspects and capabilities of both modelling methods. It has been argued that development of sound models need fit between system, problem and methodology. The success of model depends on its technical soundness as well as its successful implementation. In order to develop successful models this vision has been further extended to incorporate stakeholders, resources and time.